Outcomes of Patients With Acute Type B (DeBakey III) Aortic Dissection. Issue 8 (25th August 2015) - Afifi, Rana O.; Sandhu, Harleen K.; Leake, Samuel S.; Boutrous, Mina L.; Kumar, Varsha; Azizzadeh, Ali; Charlton-Ouw, Kristofer M.; Saqib, Naveed U.; Nguyen, Tom C.; Miller, Charles C.; Safi, Hazim J.; Estrera, Anthony L
<x xml:space="preserve">Abstract</x> Background— Aortic dissection remains the most common aortic catastrophe. In the endovascular era, the management of acute type B aortic dissection (ATBAD) is undergoing dramatic changes. The aim of this study is to evaluate the long-term outcomes of patients with ATBAD who were treated at our center over a 13-year period. Methods and Results— We reviewed patients with ATBAD between 2001 and 2014, analyzing variables based on status (complicated [c] versus uncomplicated [u]) and treatment modalities. We defined cATBAD as rupture, expansion of diameter on imaging during the admission, persistent pain, or clinical malperfusion leading to a deficit in cerebral, spinal, visceral, renal, or peripheral vascular territories at presentation or during initial hospitalization. Postoperative outcomes were defined as deficits not present before the intervention. Outcomes were compared between the groups by use of Kaplan-Meier and descriptive statistics. We treated 442 patients with ATBAD. Of those 442, 60.6% had uATBAD and were treated medically, and 39.4% had cATBAD, of whom 39.0% were treated medically to 30.0% with open repair, 21.3% with thoracic endovascular aortic repair, and 9.7% with other open peripheral procedures. Intervention-free survival at 1 and 5 years was 84.8% and 62.7% for uATBAD, 61.8% and 44.0% for cATBAD-medical, 69.2% and 47.2% for cATBAD-open, and 68.0% and 42.5% for cATBAD–thoracic endovascular aortic repair, respectively (P=0.001). Overall survival was significantly related primarily to complicated presentation. Conclusions— In our experience, early and late outcomes of ATBAD were dependent on the presence of complications, with cATBAD faring worse. Although uATBAD was associated with favorable early survival, late complications still occurred, mandating radiographic surveillance and open or endovascular interventions. Prospective trials are required to better determine the optimal therapy for uATBAD.